2017
DOI: 10.1002/psc.3062
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐like aggregation of designer bolaamphiphilic peptides: Effect of hydrophobic section and hydrophilic heads

Abstract: Amyloid-like aggregation of natural proteins or polypeptides is an important process involved in many human diseases as well as some normal biological functions. Plenty of works have been done on this ubiquitous phenomenon, but the molecular mechanism of amyloid-like aggregation has not been fully understood yet. In this study, we showed that a series of designer bolaamphiphilic peptides could undergo amyloid-like aggregation even though they didn't possess typical β-sheet secondary structure. Through systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…For example, K and R in KAAAAK (KA4K), KAAAAAAK (KA6K), and RAAAAAAR (RA6R) bolaamphiphilic peptides have hydrophilic character and are connected by the hydrophobic A residues. Their assembled product has a fibrous form [26]. Another bolaamphiphilic peptide, EFLLLLFE (EFL4FE), which contains an E residue, shows a flat membrane extension and forms peptide nanotubes by concentration differences [28].…”
Section: Self-assembling Peptides: Structure and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, K and R in KAAAAK (KA4K), KAAAAAAK (KA6K), and RAAAAAAR (RA6R) bolaamphiphilic peptides have hydrophilic character and are connected by the hydrophobic A residues. Their assembled product has a fibrous form [26]. Another bolaamphiphilic peptide, EFLLLLFE (EFL4FE), which contains an E residue, shows a flat membrane extension and forms peptide nanotubes by concentration differences [28].…”
Section: Self-assembling Peptides: Structure and Characteristicsmentioning
confidence: 99%
“…Another bolaamphiphilic peptide, EFLLLLFE (EFL4FE), which contains an E residue, shows a flat membrane extension and forms peptide nanotubes by concentration differences [28]. As the charge of amino acids is altered in different pH conditions, based on their molecular properties, these bolaamphiphilic peptides may aggregate or disaggregate according to the environmental pH [26]. Bolaamphiphiles are a category of emerging nanomaterials with the ability to self-assemble into various valuable nanostructures [49,50,51].…”
Section: Self-assembling Peptides: Structure and Characteristicsmentioning
confidence: 99%
“…Although systematic study on this issue is rare, it has been proved that solution parameters such as pH value and solvent property have critical effects on self-assembling behaviors of amphiphilic peptides. 85,86 Since it has been discussed earlier that charges in hydrophilic heads are very important for self-assembly, and the net charge of a hydrophilic amino acid is determined by the environmental pH value, it is clear that the pH value of a solution will affect the self-assembling behaviors by affecting the charges. In fact, nearly all self-assembling amphiphilic peptides have been investigated in a limited range of pH, only within which the peptide molecules could undergo self-assembly as expected.…”
Section: Solution Parametersmentioning
confidence: 99%
“…In our previous studies, we have proved that the selfassembling process of peptide monomers could be rationally controlled by deliberate peptide design, such as changing the charge distribution and geometrical shape of peptides [19][20][21] . On the other hand, environmental parameters such as pH and solvent polarity could also affect the morphology of nanostructures and their alignment 21,22 . These findings suggested that by deliberate peptide design and environment control, it's possible to fabricate desired nanostructures with controllable patterning behaviour.…”
Section: Introductionmentioning
confidence: 99%